Relationship between Organizational Strategy and Leadership Style in Performance Efficiency - Rahman, Md. Habibur; Dey, Tonmoy; Al-Amin, Md. (Asian Business Review, 2019)
The strategy of an organization reflects the probable ways to achieve the objectives of the organization. Successful organization is the result of effective implementation of organizational strategy and leadership. The study has examined the relationship between organizational strategy and leadership to achieve performance effectiveness and objectives of the organization. In this paper, extensive studies are conducted on different peer reviewed journals which is based on leadership and organizational strategy with performance. The findings of different authors are taken into consideration to show the cause effect relationship between organizational strategy and performance. This study establishes different proposition and validated those proposition with the analysis of different findings of different authors.
Keywords: Organizational strategy; leadership; performance; relationship; style